Pengaruh Tingkat Utang, Ukuran Perusahan, dan Kebijakan Dividen Terhadap Agresivitas Pajak - Endah Budiarti; Rudy, Rudy (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to examine the effect of Debt Level, Company Size, and Dividend Policy on Tax Aggressiveness in industrial companies listed on the Indonesia Stock Exchange (IDX). This type of research is quantitative and the type of data used in this study is secondary data, in the form of annual financial reports and annual reports of industrial companies in the commercial service sector for the period 2019-2023 obtained through searches on the official website of the Indonesia Stock Exchange and the official websites of the companies being researched. The research population is 35 industrial companies in the commercial service sector listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. The sample was selected using a purposive sampling technique and obtained a sample of 9 companies. The test was carried out using multiple linear regression analysis assisted by the Eviews program version 10. Debt Level is measured using total debt divided by total capital, Company Size is measured by ln = (total assets) while Dividend Policy is measured by dividends per share divided by earnings per share. From the results of the simultaneous hypothesis test (f test), Debt Level, Company Size, and Dividend Policy simultaneously or together influence Tax Aggressiveness. Based on the results of the partial test (t-test), the variables Company Size and Dividend Policy had an effect on the Tax Aggressiveness variable, while Debt Level did not have an effect on Tax Aggressiveness.